Risks and benefits of percutaneous coronary intervention in spontaneous coronary artery dissection. Issue 17 (18th May 2021) - Kotecha, Deevia; Garcia-Guimaraes, Marcos; Premawardhana, Diluka; Pellegrini, Dario; Oliver-Williams, Clare; Bountziouka, Vasiliki; Wood, Alice; Natarajan, Nalin; Jackson, Robert; Chan, Nathan; Ziaullah, Jan; Rakhit, Roby D; et al.
Abstract : Objective: To investigate percutaneous coronary intervention (PCI) practice in an international cohort of patients with spontaneous coronary artery dissection (SCAD). To explore factors associated with complications and study angiographic and longer term outcomes. Methods: SCAD patients (n=215, 94% female) who underwent PCI from three national cohort studies were investigated and compared with a matched cohort of conservatively managed SCAD patients (n=221). Results: SCAD-PCI patients were high risk at presentation with only 8.8% undergoing PCI outside the context of ST-elevation myocardial infarction/cardiac arrest, thrombolysis in myocardial infarction (TIMI) 0/1 flow or proximal dissections. PCI complications occurred in 38.6% (83/215), with 13.0% (28/215) serious complications. PCI-related complications were associated with more extensive dissections (multiple vs single American Heart Association coronary segments, OR 1.9 (95% CI: 1.06–3.39), p=0.030), more proximal dissections (proximal diameter per mm, OR 2.25 (1.38–3.67), p=0.001) and dissections with no contrast penetration of the false lumen (Yip-Saw 2 versus 1, OR 2.89 (1.12–7.43), p=0.028). SCAD-PCI involved long lengths of stent (median 46mm, IQR: 29–61mm). Despite these risks, SCAD-PCI led to angiographic improvements in those with reduced TIMI flow in 84.3% (118/140). Worsening TIMI flow was only seen in 7.0% (15/215) of SCAD-PCI patients. Post-PCI major adverse cardiovascular and cerebrovascular events (MACCE) and left ventricular function outcomes were favourable. Conclusion: While a conservative approach to revascularisation is favoured, SCAD cases with higher risk presentations may require PCI. SCAD-PCI is associated with longer stent lengths and a higher risk of complications but leads to overall improvements in coronary flow and good medium-term outcomes in patients.